Amniotic Fluid Stem Cells Prevent Development of Ascites in a Neonatal Rat Model of Necrotizing Enterocolitis - Zani, Augusto; Cananzi, Mara; Lauriti, Giuseppe; Fascetti-Leon, Francesco; Wells, Jack; Siow, Bernard; Lythgoe, Mark F.; Pierro, Agostino; Eaton, Simon; De Coppi, Paolo (European Journal of Pediatric Surgery, 2014)
Aim It has been demonstrated that in a neonatal rat model of necrotizing enterocolitis (NEC), amniotic fluid stem (AFS) cells decrease intestinal damage and improve survival via modulation of stromal cells expressing cyclooxygenase 2 in the lamina propria. Herein, we aimed to evaluate the effect of AFS cells on body weight and fluid retention in this NEC model.Methods AFS cells were obtained from green fluorescent protein (GFP) + pregnant rats at E16 and expanded in culture. A total of 185 neonatal rats had NEC induced by gavage feeding of hypertonic formula + hypoxia + oral lipopolysaccharide (4 mg/kg/d) and were randomized to intraperitoneal phosphate buffered saline (PBS, n = 93) or AFS cells (n = 92). A total of 36 breastfed (BF) rats were used as controls. All rats were being killed at 96 hours of life. Groups were compared for body weight and presence of free intraperitoneal fluid using nonparametric and contingency tests. Data are expressed as mean ± standard deviation.Results There were no differences in birth weight among the groups (PBS = 5.6 ± 0. 3 g; AFS cells = 5.6 ± 0. 3 g; BF = 5.6 ± 0. 3 g; p = 1). The body weight at randomization was not different between PBS (5.61 ± 0. 5 g) and AFS cells (5.60 ± 0. 5; p = 1) rats. After the rats were killed, BF rats were significantly heavier (12.5 ± 0.1 g) than PBS (5.12 ± 0.4 g) and AFS cell rats (4.95 ± 0.3; p < 0.0001). From randomization to being killed, PBS rats had 9% of weight loss in comparison with 12% in AFS cell rats (p = 0.08). After the rats were killed, 42 (45%) PBS rats developed ascites with evident abdominal distension in comparison with 19 (21%) AFS cells (p = 0.0005). None of BF animals had ascites.Conclusion Gavage feeding and undernutrition severely affect growth in this model of NEC. Administration of AFS cells result in lower incidence of ascites than in PBS rats. This could explain the differences in body weight between the two groups of rats that were killed. Furthermore, studies on liver function and fluid composition are needed to investigate our speculation.
Keywords: stem cell; COX-2; fetal cells; cell therapy